How long do assets last during loss of income? WSI Distribution Report 2017 - Anita Tiefensee (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2017)
A key function of assets is securing the level of consumption during loss of income. In Germany, 30 % of households can secure their current level of consumption from their assets for a few weeks or months at the most. These households have no appreciable assets at their disposal, or are even in debt. The median figure, which splits all households into two halves of equal size, is just under two years. 10 % of households can secure their current consumption for at least just under 13 years, and 5 % can even do so for more than 21 years. The securing of consumption in East Germany is markedly lower than in West Germany. Broken down into age groups, although the securing of consumption rises with age, in every age bracket at least 20 % of households could not secure their current level of consumption at all or could so for only a very short time by using up their assets. Single parents in particular are reliant on their regular income. The results show that the majority of households have only very limited private provision in the form of assets at their disposal. Generally speaking, a household's consumption can be secured on a private or state level. There should be securing of consumption on one of the two levels, otherwise major risks are not covered. There is a patent need for political action on both levels. – – Eine wichtige Funktion von Vermögen ist die Sicherung des Konsumniveaus bei Einkommensausfällen. In Deutschland können 30 % der Haushalte maximal wenige Wochen oder Monate ihr aktuelles Konsumniveau aus ihren Vermögen sichern. Diese Haushalte verfügen über kein nennenswertes Vermögen oder sind sogar verschuldet. DerMedianwert, der alle Haushalte in zwei gleich große Hälften teilt, liegt bei knapp zwei Jahren. 10 % der Haushalte können mindestens knapp 13 Jahre und 5 % sogar über 21 Jahre ihren aktuellen Konsum sichern. Die Konsumsicherung im Osten liegt deutlich unter der im Westen. Aufgeschlüsselt nach Altersgruppen zeigt sich zwar ein Anstieg der Konsumsicherung mit dem Alter, allerdings verbleiben in allen Altersklassen mindestens 20 % der Haushalte, die gar nicht oder nur sehr kurz ihr aktuelles Konsumniveau durch Verbrauch ihres Vermögens sichern könnten. Insbesondere Alleinerziehende sind auf ihr laufendes Einkommen angewiesen. Die Ergebnisse zeigen, dass die Mehrheit der Haushalte nur über eine sehr eingeschränkte private Absicherung in Form von Vermögen verfügt. Generell kann die Konsumsicherung eines Haushaltes auf privater oder staatlicher Ebene erfolgen. Auf einer der beiden Ebenen sollte eine Sicherung stattfinden, da sonst wichtige Lebensrisiken nicht abgesichert sind. Auf beiden Ebenen zeigt sich politischer Handlungsbedarf. (Vorlage)
urn:nbn:de:101:1-201801187904
Keywords: 300